PENGEMBANGAN MATERI PENDIDIKAN AGAMA ISLAM BERBASIS E-MOBILE INSTRUMENTAL - Remiswal Remiswal; Arham Junaidi Firman (POTENSIA: Jurnal Kependidikan Islam, 2020)
The rapid development of technology requires education practitioners to innove in developing materials that are integrated with technological developments. This type of research is a 4D R&D model with research subjects in Class X MIA.7 SMAN 10 Padang. The results of the study show, first, defining e-mobile instrumental-based PAI material shows the SMAN 10 Padang does not close itself from the development of the times. Second, the design of e-mobile instrumental-based PAI material is presented in two e-book variants, namely: Te-book and Se-book. Third, the test results for the validity feasibility of the material, language, contextual, presentation and  visual aspects indicate is valid. Meanwhile, the model effectiveness test is accepted at 1% significance level. Fourth, diseminate the development of PAI material based on e-mobile instrumental conducted through focus group discussion (FGD) at SMAN 10 Padang and UIN Imam Bonjol Padang.